2015
DOI: 10.1039/c5ra13176f
|View full text |Cite|
|
Sign up to set email alerts
|

Studies of intermolecular interactions in solid dispersions using advanced surface chemical analysis

Abstract: The aim of this study is to utilise an advanced surface chemical analysis based on X-ray photoelectron spectroscopy (XPS) to determine and characterise drug/polymer interactions in solid dispersions manufactured via hot melt extrusion (HME). Cetirizine HCl (CTZ) and verapamil HCl (VRP) were used as model cationic drugs while Eudragit® grade L100 and L100-55 polymers were used as anionic carriers. A molecular dynamics (MD) based simulation approach predicted drug/polymer interactions while scanning electron mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 32 publications
2
14
0
Order By: Relevance
“…The calculated low N coefficient values in the formulations revealed that the interactions between the drug and polymers are quite strong. It has been reported that the lower N coefficient value leads to a high number of protonated N atoms that take part in the interactions making it stronger [27][28][29][30].…”
Section: Surface Elemental Analysis Via Xpsmentioning
confidence: 99%
“…The calculated low N coefficient values in the formulations revealed that the interactions between the drug and polymers are quite strong. It has been reported that the lower N coefficient value leads to a high number of protonated N atoms that take part in the interactions making it stronger [27][28][29][30].…”
Section: Surface Elemental Analysis Via Xpsmentioning
confidence: 99%
“…Similar results were found in one of our previously reported study [20]. Moreover, EDS analysis was performed to map the distribution of IBU and homogeneity of the composite granules [24,25]. Both the drug and polymeric career used in this study mainly contain C and O atoms likewise most of the polymers.…”
Section: Particle Size and Morphologysupporting
confidence: 85%
“…Maniruzzaman et al (2015) used the Flory-Huggins (F-H) lattice-based theory to explain intermolecular interactions between polymer and API is limited as it does not take into consideration the various multiple interactions in drug-polymer systems [20]. Therefore, the HSPs developed by Van Krevelen and Hoftyzer group were used as a substitute for the Flory-Huggins theory to explore the nature of interactions that occur within drug-polymer systems and is mainly based upon the chemical structures of each of the pure components.…”
Section: Pre-formulation Studiesmentioning
confidence: 99%
“…where ∆G mix , ∆H mix , ∆S mix and T are the Gibbs free energy, enthalpy of mixing, entropy of mixing and absolute temperature, respectively. The free energy change is spontaneous as a result of the increase in entropy of mixing and is therefore negative [20]. However, the presence of repulsive and cohesive intermolecular and intramolecular forces (e.g., dispersion force, hydrogen bonding and dipole-dipole interaction) which are present within the amorphous SD, making the intermolecular interaction between drug and polymer more complex.…”
Section: Pre-formulation Studiesmentioning
confidence: 99%
See 1 more Smart Citation